2021
DOI: 10.3390/molecules26020357
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antibacterial, and Antioxidant Evaluation of Novel Series of Condensed Thiazoloquinazoline with Pyrido, Pyrano, and Benzol Moieties as Five- and Six-Membered Heterocycle Derivatives

Abstract: A novel synthesis of thiazolo[2,3-b]quinazolines 4(a–e), pyrido[2′,3′:4,5]thiazolo[2,3-b]quinazolines {5(a–e), 6(a–e), and 7(a–e)}, pyrano[2′,3′:4,5]thiazolo[2,3-b]quinazolines 8(a–e), and benzo[4,5]thiazolo[2,3-b]quinazoloine9(a–e) derivatives starting from 2-(Bis-methylsulfanyl-methylene)-5,5-dimethyl-cyclohexane-1,3-dione 2 as efficient α,α dioxoketen dithioacetal is reported and the synthetic approaches of these types of compounds will provide an innovative molecular framework to the designing of new activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Heterocyclic structures having a nitrogen bicyclic nucleus such as quinzolines and octahydroquinazolines are the pioneers for the development of a large number of drugs, and several researchers around the world have also focused on other studies [ 7 ]. Recently, octahydroquinazoline scaffolds have been reported with a variety of medicinal properties, including anticancer [ 8 ], anti-inflammatory [ 9 ], and antimicrobial [ 10 ]. The acid-catalyzed cyclocondensation of aldehydes, ethylacetoacetate, and urea to produce octahydroquinazoline is a well-known Bigineli type of reaction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic structures having a nitrogen bicyclic nucleus such as quinzolines and octahydroquinazolines are the pioneers for the development of a large number of drugs, and several researchers around the world have also focused on other studies [ 7 ]. Recently, octahydroquinazoline scaffolds have been reported with a variety of medicinal properties, including anticancer [ 8 ], anti-inflammatory [ 9 ], and antimicrobial [ 10 ]. The acid-catalyzed cyclocondensation of aldehydes, ethylacetoacetate, and urea to produce octahydroquinazoline is a well-known Bigineli type of reaction [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant compounds also have functional importance in biological activities and in the pharmaceutical industries as radical scavengers [13,14] . In this study, antioxidant compounds were synthesized from the reaction of thiols with alkene compound such as, eugenol and then added them to industrial lubricating oils, and the oxidative stability of oils was observed.…”
Section: Introductionmentioning
confidence: 99%